Guyana. Significant achievements 2021 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Guyana during 2021 are identified, with respect to the needs and interests of the country, strengthening the livestock industry, the dairy production industry, the value chain of rice farming, crop management, vegetable seed production, food sanitation and safety, energy efficiency and resilience against climate change. Likewise, support was provided in post-COVID-19 care, as well as support for farmers who suffered losses caused by the floods. Finally, work was done on improving international trade and economic development; as well as in the implementation of new technologies in agriculture, such as drones and satellites.